Ion source of reactive gases with decreased neutral gas inleakage - Lymar, A.G.; Martynenko, P.A.; Pоpоv, V.A. (Вопросы атомной науки и техники, 2005)
Ion source with an original system of ions extraction from the discharge chamber, allowing more then on order of magnitude reducing of neutral gas incoming to the chamber of ion beam acceleration and use is described. The parameters of a received beam of nitrogen ions and possible variants of the source application have been given. Описано іонне джерело із оригінальною системою добування іонів з розрядної камери, що дозволяє більш ніж на порядок знизити надходження нейтрального газу в камеру прискорення і використання іонного пучка. Приведені параметри отриманих пучків іонів азоту та можливі варіанти застосування таких джерел. Описан ионный источник с оригинальной системой извлечения ионов из разрядной камеры, позволяющей более чем на порядок снизить натекание нейтрального газа в камеру ускорения и использования ионного пучка. Приведены параметры получаемых пучков ионов азота и возможные варианты применения таких источников.